Obesity: effects of physical exercise and metformin on metabolic aspects of monosodium glutamate treated rats - Curiacos de Almeida Leme, Jose Alexandre [UNESP]; Silveira, Rafael Fernando [UNESP]; Manchado-Gobatto, Fulm de Barros [UNESP]; de Alencar Mota, Clecia Soares [UNESP]; Gomes, Ricardo Jose [UNESP]; Rostom de Mello, Maria Alice [UNESP]; Luciano, Eliete [UNESP] (Editrice Kurtis S R L, 2009)
The present study investigated the effects of swimming training and metformin on metabolic aspects of obese rats. Wistar rats were divided into control (C), obese (O), Trained Obese (TO) and metformin obese (MO) groups. Obesity was induced by subcutaneous monosodium glutamate injection (4 mg/g body weight). Exercise program consisted in swimming 1 h/day, 5 days/week, for 8 weeks, supporting a load corresponding to 5% of body weight. Metformin was dissolved in the drinking water (1.4 mg/ml) for 8 weeks. At the end of the experimental period, rats were sacrificed and blood was collected for determinations of serum glucose, insulin and triglycerides and hematocrit. Samples of gastrocnemius muscle and liver were removed to evaluate triglycerides content MSG-induced obesity, increased serum glucose, insulin and triglycerides, while physical training was able to recover serum glucose and insulin and metformin treatment recovered serum insulin and slightly reduced the serum glucose. MSG-induced obesity also increased liver triglycerides content and physical training and metformin administration recovered these parameters. It was concluded that in MSG obese rats, physical exercise and metformin induced important metabolic alterations associated with an improvement in glucose homeostasis and in liver fat content. Obesity and Metabolism 2009; 5: 129-133.
Keywords: Exercise and metabolism; metformin; obesity